Differences between CO- and calcium triplet-derived velocity dispersions in spiral galaxies: evidence for central star formation?. Issue 3 (28th November 2014) - Riffel, Rogemar A.; Ho, Luis C.; Mason, Rachel; Rodríguez-Ardila, Alberto; Martins, Lucimara; Riffel, Rogério; Diaz, Ruben; Colina, Luis; Alonso-Herrero, Almudena; Flohic, Helene; Martin, Omaira Gonzalez; Lira, Paulina; et al.
Abstract: We examine the stellar velocity dispersions (σ) of a sample of 48 galaxies, 35 of which are spirals, from the Palomar nearby galaxy survey. It is known that for ultra-luminous infrared galaxies (ULIRGs) and merger remnants, the σ derived from the near-infrared CO band heads is smaller than that measured from optical lines, while no discrepancy between these measurements is found for early-type galaxies. No such studies are available for spiral galaxies – the subject of this paper. We used cross-dispersed spectroscopic data obtained with the Gemini Near-Infrared Spectrograph, with spectral coverage from 0.85 to 2.5 μm, to obtain σ measurements from the 2.29 μm CO band heads (σCO ) and the 0.85 μm calcium triplet (σCaT ). For the spiral galaxies in the sample, we found that σCO is smaller than σCaT, with a mean fractional difference of 14.3 per cent. The best fit to the data is given by σopt = (46.0 ± 18.1) + (0.85 ± 0.12)σCO . This 'σ-discrepancy' may be related to the presence of warm dust, as suggested by a slight correlation between the discrepancy and the infrared luminosity. This is consistent with studies that have found no σ-discrepancy in dust-poor early-type galaxies, and a much larger discrepancy in dusty merger remnants and ULIRGs. That σCO is lower than σopt may also indicate the presence of a dynamically cold stellar population component. This would agree with the spatial correspondence between low-σCO and young/intermediate-age stellar populations that has been observed in spatially resolved spectroscopy of a handful of galaxies.